Teaching Critical Media Literacy in Adult and Higher Education: An Action Research Study - Elizabeth J. Tisdell; Heather L. Stuckey; Patricia M. Thompson (Adult Education Research Conference, 2007)
This paper discusses three findings of critical media literacy study: pleasure as a motivator and deterrent to becoming critical; the importance of facilitated discussion; and learning from application to practice.